Information visualization - Ling, Daniel Hock Hin (2014)
Often in schools, students are given the opportunity to learn about plants under General Science. This project goes through the information visualization process on plant dataset. Choropleth map, heat matrix and coordinated view were integrated into a webpage and presented as a potential tool for educational purposes. The implemented visualizations were fairly effective, able to maximize space and minimize noise. Performance and memory utilization are some of the non-critical aspects, which may require further improvement.